KEMAMPUAN LITERASI SAINS SISWA PADA MATERI PERUBAHAN LINGKUNGAN DI SMAN 1 PASIR PENYU - Dita Aldeasari Nurrizki; Yuslim Fauziah; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The challenges of 21st century learning require the learning process to be more active. Conventional learning methods are still widely used in various learning so that student interaction in learning is still very low. One of the abilities that students must have in this 21st century learning is scientific literacy skills, namely the ability of students to use scientific knowledge, identify problems and draw conclusions based on scientific evidence in making decisions. The results of the PISA study show that the scientific literacy of Indonesian students is in the